2019
DOI: 10.52306/02010319lfqz1592
|View full text |Cite
|
Sign up to set email alerts
|

Examining Perceptions of Online Harassment among Constables in England and Wales

Abstract: The ubiquity of the Internet and computer technology has enabled individuals to engage in bullying, threats, and harassing communications online. Limited research has found that local line officers may not view these offenses as serious compared to real world crimes despite their negative physical and emotional impact on victims. The perceptions of officers can produce poor interactions with victims during calls for service, particularly victim blaming, which can reduce citizens’ confidence in police agencies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…While this study highlighted the negative treatment of victims by the police, it also found that over half of the sample population (54%) reported positive victim experiences with the police, rendering the results as mixed and inconclusive. Holt et al (2019) confirmed that dismissive responses to victims could be strongly related to police officers having negative attitudes about cyberstalking-in the sense that they believe that online offences could be avoided and are not serious enough to demand police attention. However, the survey data gathered in this study did not consider the range of constabulary policies (or lack of) around stalking and how they may contribute to police officer understandings and responses to victims.…”
Section: Victim Experiences With the Criminal Justice Systemmentioning
confidence: 71%
See 2 more Smart Citations
“…While this study highlighted the negative treatment of victims by the police, it also found that over half of the sample population (54%) reported positive victim experiences with the police, rendering the results as mixed and inconclusive. Holt et al (2019) confirmed that dismissive responses to victims could be strongly related to police officers having negative attitudes about cyberstalking-in the sense that they believe that online offences could be avoided and are not serious enough to demand police attention. However, the survey data gathered in this study did not consider the range of constabulary policies (or lack of) around stalking and how they may contribute to police officer understandings and responses to victims.…”
Section: Victim Experiences With the Criminal Justice Systemmentioning
confidence: 71%
“…Holt et al (2019) confirmed that dismissive responses to victims could be strongly related to police officers having negative attitudes about cyberstalking—in the sense that they believe that online offences could be avoided and are not serious enough to demand police attention. However, the survey data gathered in this study did not consider the range of constabulary policies (or lack of) around stalking and how they may contribute to police officer understandings and responses to victims.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Extant literature has suggested a significant relationship between individuals' skill and comfort with technology and their perceptions of cybercrime seriousness. Specifically, research has found that law enforcement officers with more experience and comfort with technology were significantly more likely to perceive cybercrime as serious given their heightened awareness of the potential risks and consequences associated with online offences (e.g., Hinduja, 2007;Holt et al, 2019;Leukfeldt et al, 2013). In fact, individuals who enjoy using technology, feel comfortable in online settings, and are confident with using digital technology, would be more likely to understand the different types of misconduct that arise in online settings and its potential risks and consequences.…”
Section: Predictors Of Crime Seriousnessmentioning
confidence: 99%
“…A failure to both identify cybercrime behaviours and adequately understand their consequences may affect several behavioural outcomes, including individuals' reporting and helpseeking behaviours, bystander interventions, and even willingness to offend (see Holt et al, 2019;Horgan et al, 2021;Lee et al, 2021). Relatedly, this lack of understanding may affect individuals' perceptions of cybercrime seriousness, which may equate to a lower allocation of public funds and law enforcement resources to combat such misconduct (see Koziarski & Lee, 2020;Lee, 2022), and reduce support for policies that advocate for greater online crime prevention efforts (Dodge & Burruss, 2019;Yar, 2013).…”
Section: Introductionmentioning
confidence: 99%